IPOs and Stock Returns: The Role of Capital Structure, Firm Size, Profitability, and Firm Value - Andiyanto, Stevanus; Amir, Amir; Setyadi, Edi Joko; Santoso, Selamet Eko Budi (E-Jurnal Akuntansi, 2025)
The purpose of this study is to empirically examine the relationship between stock returns and capital structure, firm size, profitability, and firm value. The population in this study were companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (IDX) between 2020 and 2023. The sample was determined using a purposive sampling method. Data were analyzed using panel data analysis techniques. The results of this study found evidence that company size has a positive effect on stock returns, while capital structure and profitability have no effect on stock returns, and firm value has a negative effect on stock returns. The implications of these results suggest that companies planning to go public should pay attention to business scale and maintain a healthy financial structure to increase their attractiveness to investors. For investors, it is important to not only pay attention to market value but also to assess the company's overall business quality and viability before making investment decisions, particularly for IPO stocks that tend to be volatile. Keywords: Stock Return; Capital Structure; Company Size; Profitability: Company value